Hubungan Celebrity Endorser, Iklan, dan Ulasan Produk dengan Minat Beli Konsumen Brand ESQA di Shopee - Dhavinna Fahira Adrika; Fajar Adi Prakoso (eCo-Buss, 2026)
This study is motivated by the increasing competition in the e-commerce industry, which encourages companies to implement effective marketing strategies to attract consumer purchase intention. Celebrity endorsers, advertising, and product reviews are commonly used as promotional tools in online marketplaces such as Shopee. This study aims to analyse the relationship between celebrity endorser, advertising, and product reviews with consumers’ purchase intention toward ESQA brand on the Shopee platform. The research employed a quantitative approach using a survey method. The population of this study consisted of consumers who have purchased ESQA products on Shopee, with a sample of 120 respondents selected using purposive sampling. The findings indicate that celebrity endorser and advertising have a positive relationship with consumers purchase intention, while product reviews show a negative relationship with purchase intention toward the ESQA brand on Shopee. These results suggest that promotional strategies involving credible endorsers and attractive advertising play an important role in influencing consumer interest, whereas product reviews may reduce purchase intention under certain conditions. In conclusion, this study highlights the importance of optimizing celebrity endorsement and advertising strategies to enhance consumers purchase intention on Shopee